Modeling Stunting Reduction Policies Through PLS-SEM Using Socioeconomic Factors In East Kalimantan - Muhammad Alfarizi; Suci Megawati (Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur, 2026)
Objective: Stunting remains a critical public health and development issue, particularly in developing regions where socioeconomic disparities persist. Despite significant economic growth, East Kalimantan Province continues to experience relatively high and uneven stunting rates across its regencies and cities. This condition indicates that stunting is not merely a nutritional problem but a multidimensional issue influenced by broader socioeconomic factors. The main problem addressed in this study is the limited understanding of how regional socioeconomic determinants interact structurally to influence stunting reduction. Therefore, this study aims to develop a comprehensive policy model for reducing stunting based on community socioeconomic factors using a structural approach. Design/Methods/Approach: This research employs a quantitative design using secondary data from the Central Statistics Agency (BPS) and related institutions for 2020–2025. The unit of analysis consists of regencies and cities in East Kalimantan. Partial Least Squares Structural Equation Modeling (PLS-SEM) is applied to analyze both direct and indirect relationships among variables, including regional health expenditure, maternal education, sanitation, Human Development Index (HDI), and stunting reduction. Findings: The results indicate that all proposed hypotheses are supported. Regional health expenditure, maternal education, and sanitation have positive and significant effects on HDI, with maternal education emerging as the strongest determinant. Furthermore, HDI has a significant negative effect on stunting, confirming its mediating role in translating socioeconomic improvements into better child health outcomes. Originality/Value: The model demonstrates strong explanatory power for HDI but more limited capacity in explaining stunting reduction directly. In general, the findings imply that effective stunting reduction policies must adopt an integrated, multisectoral approach focusing on improving quality of life. Practical/Policy implication: Policy priorities should emphasize strengthening maternal education, enhancing preventive health spending, and expanding access to sanitation. These strategies are essential for accelerating sustainable stunting reduction at the regional level.